Uji Aktivitas Formulasi Mikrokapsul Ekstrak Etanol Herba Sirih Cina (Peperomia pellucida L.) Sebagai Antidislipidemia terhadap Tikus Putih - Ricky Martino; Razoki Razoki; Muhammad Yunus (Quantum Wellness : Jurnal Ilmu Kesehatan, 2025)
Dyslipidemia is a lipid metabolism disorder characterized by an increase or decrease in blood plasma fat levels. This condition includes high levels of total cholesterol, low-density lipoprotein (LDL), and triglycerides, as well as decreased levels of high-density lipoprotein (HDL). In general, dyslipidemia is divided into two types: primary, which is influenced by genetic factors, and secondary, which is caused by other diseases or an unhealthy lifestyle. Dyslipidemia is one of the major risk factors for cardiovascular disease, making its prevention and treatment very important. In this study, male white mice were used and induced with a high-fat diet to trigger dyslipidemia. The test animals were then divided into six groups: a negative control, a positive control (given simvastatin at a dose of 0.36 mL/day), and three treatment groups with microcapsules of Chinese betel leaf herb ethanol extract (EEHSC) at concentrations of 0.25%, 0.5%, and 0.75%. The treatment was administered orally for 14 days. Cholesterol levels were measured before and after treatment using a digital cholesterol tester and laboratory analysis to ensure more accurate results. The results showed a decrease in cholesterol levels with varying percentages in each group. The negative control decreased by 24.8%, the positive control by 36.1%, the 0.25% EEHSC by 24.1%, the 0.5% EEHSC by 34.7%, and the 0.75% EEHSC by 45.5%. This indicates that the 0.5% EEHSC treatment produced cholesterol reductions almost comparable to simvastatin. Interestingly, the highest effect was observed in the 0.75% group, indicating a dose-dependent response. In contrast, the 0.25% concentration only produced a less than optimal effect. Thus, microcapsules of ethanol extract of the Chinese betel leaf herb have potential as an alternative agent for lowering cholesterol levels, particularly in dyslipidemia. These findings suggest that natural-based therapies could complement conventional treatments in managing lipid disorders.